Effect of Season, Transport Length, Deck Location, and Lairage Length on Pork Quality and Blood Cortisol Concentrations of Market Hogs - David Newman; Jennifer Young; Chad Carr; Matt Ryan; Eric Berg (Animals, 2014)
The objective of this study was to investigate the effects of seasonal environment, transport conditions, and time in lairage on pork quality and serum cortisol concentrations. Market hogs were slaughtered during winter (n = 535), spring (n = 645), summer (n = 644), and fall (n = 488). Within season, hogs were randomly assigned to treatments in a 2 × 2 × 2 factorial arrangement, with 2 deck locations (top vs. bottom) and 2 transport and lairage durations (3 h vs. 6 h). Blood samples were collected at exsanguination for analysis of cortisol concentration. Loins were collected at 24 h postmortem for pork quality assessment. Season and deck did not have a main effect on cortisol concentrations or pork quality. Hogs transported 6 h had increased cortisol concentrations (103.0 vs. 95.5 ng/mL; P < 0.001) and decreased L* (52.49 vs. 52.69; P = 0.09), b* (6.28 vs. 6.36; P = 0.03), and hue angle (20.70 vs. 20.95; P = 0.03) compared to hogs transported 3 h. Hogs subjected to 6 h of lairage had increased 24-h pH (5.69 vs. 5.66; P = 0.005), a* (16.64 vs. 16.48; P < 0.0001), b* (6.42 vs. 6.22; P < 0.0001), saturation (17.85 vs. 17.64; P < 0.0001), and hue angle (21.01 vs. 20.65; P = 0.002) and decreased L* (52.49 vs. 52.69; P = 0.07) when compared to hogs subjected to 3 h of lairage.